2010
DOI: 10.1038/ja.2010.11
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids from a deep ocean sediment-derived fungus Penicillium sp. and their antitumor activities

Abstract: Four new alkaloids, including two new meleagrin analogs, meleagrin D (1) and E (2), and two new diketopiperazines, roquefortine H (3) and I (4), were isolated from a deep ocean sediment-derived fungus Penicillium sp. Meleagrin D (1) and E (2) possess unprecedented acetate-mevalonate-derived side chains on the imidazole moiety. These new meleagrins showed weak cytotoxicity against the A-549 cell line, whereas meleagrin B (5) and meleagrin (6), which were isolated previously from the same strain, induced HL-60 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 17 publications
1
62
0
Order By: Relevance
“…Peak 57 (RT=10.1 min, C 23 H 23 N 5 O 4 ) in extracts 2 and 3 displayed UV maxima at 230 and 330 nm, agreeing with its hit, meleagrin, a cytotoxic alkaloid from two Penicillium species (Du et al, 2010). Additionally, possible derivatives of meleagrin, including oxaline (also cytotoxic), neoxaline, and 9-epineoxaline, were found in extracts 4 and 2 with peak numbers of 67, 46 or 49, and 49 or 46, respectively; besides, several possible roquefortine (oxaline's precursor) analogues were also detected in extracts 4, 7, and 21, with peak numbers of 62 ( N 6 -formylroquefortine C), 68 (roquefortine C), and 81(roquefortine F), respectively (Pieter and Robert, 1983).…”
Section: To Be Continuedsupporting
confidence: 68%
“…Peak 57 (RT=10.1 min, C 23 H 23 N 5 O 4 ) in extracts 2 and 3 displayed UV maxima at 230 and 330 nm, agreeing with its hit, meleagrin, a cytotoxic alkaloid from two Penicillium species (Du et al, 2010). Additionally, possible derivatives of meleagrin, including oxaline (also cytotoxic), neoxaline, and 9-epineoxaline, were found in extracts 4 and 2 with peak numbers of 67, 46 or 49, and 49 or 46, respectively; besides, several possible roquefortine (oxaline's precursor) analogues were also detected in extracts 4, 7, and 21, with peak numbers of 62 ( N 6 -formylroquefortine C), 68 (roquefortine C), and 81(roquefortine F), respectively (Pieter and Robert, 1983).…”
Section: To Be Continuedsupporting
confidence: 68%
“…DKPs have been isolated from various microorganisms, such as from fungi like Fusarium oxysporum (Trigos et al 1995), Porphyra yezoensis (Byun et al 2003), and Penicillium sp. (Du et al 2010); and from bacteria like Pseudomonas spp. (Degrassi et al 2002;Holden et al 1999;Musthafa et al 2012), Pseudoalteromonas spp.…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial capsular polysaccharide was found to inhibit many bacteria biofilm formation (Goncalves et al 2014), and a set of proteases immobilized on chitosan showed anti-biofilm activities on several pathogenic bacteria (Elchinger et al 2014). Diketopiperazines (DKPs), otherwise referred as cyclic dipeptides, have attracted the attention of microbial researchers for their biological activities including antibacterial (Prasad 1995;Qi et al 2009;De Carvalho and Abraham 2012;ElGendy and Rateb 2015), antifungal (Byun et al 2003), antifouling (Li et al 2006), antilarval (Qi et al 2009), and antitumor (Du et al 2010;Wang et al 2015) activities. DKPs have been isolated from various microorganisms, such as from fungi like Fusarium oxysporum (Trigos et al 1995), Porphyra yezoensis (Byun et al 2003), and Penicillium sp.…”
Section: Introductionmentioning
confidence: 99%
“…Compound 3 was isolated as pale yellow needles and assigned the molecular formula C 21 and between H-8 and H-9 (10.9 Hz) also suggested the same relative congurations of C-7, C-8 and C-9 as 1 ( Table 1). The absolute conguration of 3 was also deduced by the X-ray singlecrystal diffraction experiment (Cu Ka radiation (l ¼ 1.54184 A); Flack parameter 0.05(11)) (Fig.…”
Section: -13mentioning
confidence: 99%